The characteristics of pressure recovery in an adjustable ejector multi-evaporator refrigeration system - Lin, Chen (2013)
In this paper, Computational Fluid Dynamics (CFD) technique is used to investigate the adaption of adjustable ejector for variable cooling loads and the characteristics of ejector pressure recovery in a multi-evaporator refrigeration system (EMERS) using R134a as the refrigerant. The performance of pressure recovery reflects the performance of the compression energy saving. The developed CFD model is first validated by actual experimental data of an EMERS (ejector-based multi-evaporator refrigeration system). Turbulence model constants are carefully selected in order to minimize the model prediction error. The calibrated model is then solved to find the adaption property of the adjustable ejector and the effects of varying cooling loads on and the pressure recovery ratio. The results indicate that the adjustable ejector using spindle to adjust the throat area of primary nozzle is an efficient solution to control the primary operating pressure in constant for system stability. Pressure recovery ratio is sensitive to the varying of cooling loads and the relationship between them is then presented.